Homologous Lympho-epithelial Kazal-type inhibitor domains delay blood coagulation by inhibiting factor X and XI with differential specificity - Ramesh, Karthik (2020)
Despite being initially identified in the blood filtrate, LEKTI is a 15-domain Kazal-type inhibitor mostly known in the regulation of skin desquamation. In the current study, screening of serine proteases in blood coagulation cascade showed that LEKTI domain 4 has inhibitory activity toward only FXIa, whereas LEKTI domain 6 inhibits both FXIa and FXaB (bovine FXa). Nuclear magnetic resonance structural and dynamic experiments plus molecular dynamics simulation revealed that LEKTI domain 4 has enhanced backbone flexibility at the reactive-site loop. A model of the LEKTI-protease complex revealed that FXaB has a narrower S4 pocket compared with FXIa and hence prefers only small side-chain residues at the P4 position, such as Ala in LEKTI domain 6. Mutational studies combined with a molecular complex model suggest that both a more flexible reactive-site loop and a bulky residue at the P4 position make LEKTI domain 4 a weaker but highly selective inhibitor of FXIa.